Randomized comparison of stapled haemorrhoidopexy and open haemorrhoidectomy - Rulaniya, Suresh Kumar; Chandra, Soumitra (International Surgery Journal, 2018)
Background: Surgical management of haemorrhoids is reserved for stage III and IV haemorrhoids. Both Milligan-Morgan technique (CH-Conventional Haemorrhoidectomy) and stapled haemorrhoidopexy technique are used as surgical therapy. Our prospective, comparative study of conventional haemorrhoidectomy versus stapled haemorrhoidectomy was designed in present institution. Methods: This prospective randomised comparative study was carried out in present Surgery Dept from July 2016 to December 2017 with total 60 sample size. All data were analysed according to applicable statistical methods. The results were compared to previous studies so as to arrive at a conclusion. Results: The mean duration of surgery with stapled method was 30.76±3.13 minutes and with conventional method was 49.36±4.08 minutes which was significantly high in conventional method. VAS scores for pain at 12 hours, 24 hours, 72 hours and 7 days for stapled group were 2.63±0.76, 1.66±0.88, 0.90±0.71 and 0.50±0.43 while that for the conventional group were 5.63±0.72, 4.56±1.22, 3.26±1.25 and 2.00±0.69. At all points of time the VAS was significantly lower in stapled group. The mean duration of hospital stay of the patients with stapled method was 3.10±0.75 days and with conventional method was 6.06±0.94 days, which was significantly high in conventional method. The mean time to return to normal activities of the patients with stapled method was 8.16±1.93 days and with conventional method was 12.60±1.67 days, which also significantly high in conventional method. Conclusions: Present study inferred that stapled haemorrhoidopexy is faster, minimally invasive for treatment of haemorrhoids as compared to Conventional haemorrhoidectomy. It is associated less pain and provides a more satisfactory alternative to Conventional surgery because of reduced hospitalisation and earlier return of patient to daily activities, with no significant differences in short term follow up.